The impact of digital marketing, product quality, and reference groups on purchasing decisions at the Eiger Store Bukittinggi - Muhammad Arbian; Awisal Fasyni (Universitas Negeri Padang, 2023)
This research aims to analyze Digital Influence Marketing , Product Quality, as well Reference Groups on Purchasing Decisions. This research is classified as porposive sampling , the sample in this research is Eiger Store Bukittinggi customers with the following criteria : a ) Consumers of outdoor equipment products. b) Have made purchases of outdoor equipment products in the city of Bukittinggi or West Sumatra. c) Customers who have seen digital marketing from the Eiger Store in Bukittinggi City. While the number of samples in This study consisted of 160 samples using purposive sampling. The data analysis technique is a regression analysis technique using the SPSS V.25 application. The results of this study are as follows: 1) There is a significant influence between Digital Marketing on Purchasing Decisions. 2) There is a significant influence between Product Quality on Purchasing Decisions. 3) There is a significant influence between the Reference Group on Purchasing Decisions.